Construction of the Practical Evaluation System of the Advanced Foreign Language Curriculum Based on CAI - Shi Xiaojuan (Journal of Information & Systems Management, 2017)
From the beginning of twentieth Century, the construction of education evaluation system had become an independent research field, which has aroused the concern of the educational fields in our country. Today this practical evaluation system has become an important subject in the reform and development in national advanced education. Since computer aided institution emerged, it was quickly applied in the construction of the practical evaluation system of the advanced foreign language curriculum. In this article, we will analyze the construction of practical evaluation system based on CAI in the advanced foreign language curriculum through the evaluation criteria and the results of evaluation system. And summarized that the evaluation result can help to promote the effectiveness of the advanced foreign language curriculum thus it can monitor the practical learning statement of the students throw CAI.